Pengembangan Modul Hakikat Fisika Berbasis Problem Based Learning untuk Memfasilitasi Literasi Sains Siswa Kelas X SMA - Geby Anita; Ahmad Amin; Yaspin Yolanda (Proceeding of Silampari Conference of Life Science and Technology, 2026)
learning to enable students to understand scientific concepts, explain scientific phenomena, and apply their knowledge to solve real-life problems. However, physics instruction in schools is still dominated by teaching materials that emphasize concept delivery, limiting students' opportunities to develop scientific literacy. This study aimed to develop a Problem Based Learning (PBL)-based module on the Nature of Physics as scientific literacy-oriented teaching material for tenth-grade senior high school students. The study employed a Research and Development (R&D) approach using the Four-D (4D) development model, which consists of the define, design, develop, and disseminate stages. The research instruments included expert validation sheets for material, media, and language, as well as a scientific literacy test. The module was designed by integrating the syntax of Problem Based Learning into each learning activity to provide students with meaningful learning experiences through contextual problem solving. The developed module is expected to serve as valid, practical, and effective teaching material to support physics learning and facilitate the development of students' scientific literacy.